Comportamiento agronómico de maní (Arachis hypogaea l.) con abonos orgánicos en la parroquia El Carmen cantón La Maná - Chasiluisa Salazar, Mariela del Pilar (2015)
In the agronomic behavior of peanut (Arachis hypogaea L.) with two organic fertilizers in El Carmen Parish, La Maná Canton objectives, it determine the agronomic behavior of peanut (Arachis hypogaea L.), know the best organic fertilizer for the production of peanuts, relationship benefit/cost of treatments. Using the the complete block design with a factorial arrangement (DBCA) random, varieties of peanuts (caramelo and rosita), factor b organic fertilizers (vermicompost and water hyacinth) with four treatments and five replications and twenty experimental units....